Solve for x
x=4
Graph
Share
Copied to clipboard
x-\left(5+3x-\left(5x-6-x\right)\right)=-3
To find the opposite of 6+x, find the opposite of each term.
x-\left(5+3x-\left(4x-6\right)\right)=-3
Combine 5x and -x to get 4x.
x-\left(5+3x-4x-\left(-6\right)\right)=-3
To find the opposite of 4x-6, find the opposite of each term.
x-\left(5+3x-4x+6\right)=-3
The opposite of -6 is 6.
x-\left(5-x+6\right)=-3
Combine 3x and -4x to get -x.
x-\left(11-x\right)=-3
Add 5 and 6 to get 11.
x-11-\left(-x\right)=-3
To find the opposite of 11-x, find the opposite of each term.
x-11+x=-3
The opposite of -x is x.
2x-11=-3
Combine x and x to get 2x.
2x=-3+11
Add 11 to both sides.
2x=8
Add -3 and 11 to get 8.
x=\frac{8}{2}
Divide both sides by 2.
x=4
Divide 8 by 2 to get 4.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}